Low Temperature Affects Stem Cell Maintenance in Brassica oleracea Seedlings - de Jonge, Jennifer; Kodde, Jan; Severing, Edouard I.; Bonnema, Guusje; Angenent, Gerco C.; Immink, Richard G. H.; Groot, Steven P. C. (Frontiers in Plant Science, 2016)
Most of the above ground tissues in higher plants originate from stem cells located in the shoot apical meristem (SAM). Brassica oleracea plants can suffer from spontaneous stem cell arrest resulting in lack of further shoot development. This SAM arrest is known as blindness and occurs in an unpredictable manner leading to considerable economic losses for plant raisers and farmers. Detailed analyses of seedlings showed that stem cell arrest is triggered by low temperatures during germination. To induce this arrest reproducibly with sensitive seed lots and to study the effect of environmental parameters genetic variation for susceptibility was analyzed by a quantitative genetic mapping approach revealing a region on linkage groups C3 associated with blindness sensitivity. A subsequent dynamic genome-wide transcriptome analysis resulted in the identification of around 3000 differentially expressed genes early after blindness induction. A large number of cell cycle genes are en masse induced early during the development of blindness, whereas shortly after, all were down-regulated. This miss-regulation of core cell cycle genes is accompanied with a strong reduction of cells reaching the DNA replication phase. From the differentially expressed genes, 90 were located in QTL region C3. Among them are two genes belonging to the MINICHROMOSOMAL MAINTENANCE (MCM) gene family, known to be involved in DNA replication, a RETINOBLASTOMA-RELATED (RBR) gene, a key regulator for cell cycle initiation, and several MutS homologues (MSH) genes, involved in DNA repair. These genes are potential candidates for being involved in the development of blindness in sensitive genotypes